Patient-centered treatment in atrial fibrillation. Issue 12 (December 2016) - Cox, Mary C.; Gulati, Vijay K.
Abstract : ABSTRACT: Patients with atrial fibrillation (AF) and clinicians treating them are faced with innumerable management choices. Minimizing thromboembolic events and strokes related to AF is paramount. Estimating the risks with the various therapies is important for optimal therapy. Also, patients must choose a rate control or a rhythm control strategy. With so many options, clinical presentations, and patient desires, patients with AF are rarely treated identically. This allows for shared decision-making and patient-centered care.